Low vaccination and infection rate of Omicron in patients with inflammatory bowel disease: a comparative study of three unique cohorts - Jing Feng; Tian Yang; Ruchen Yao; Bo Feng; Bo Feng; Renshan Hao; Renshan Hao; Yuqi Qiao; Jinlu Tong; Jun Shen; Jun Shen (Frontiers Media S.A., 2023)
BackgroundThe SARS-CoV-2 Omicron variant caused a large-scale outbreak of COVID-19 in Shanghai, China. Patients with inflammatory bowel disease (IBD) are at high risk of infection due to immunosuppressive interventions. We aimed to investigate the vaccination information of patients with IBD and update a vaccination guide based on a comparison of vaccination in asymptomatic carriers and healthy individuals.MethodsThis retrospective study was conducted during an Omicron variant wave. We assessed the vaccination status in patients with IBD, asymptomatic carriers and healthy individuals. Factors with unvaccinated status and adverse events following vaccination were also determined in patients with IBD.ResultsThe vaccination rate was 51.2% in patients with IBD, 73.2% in asymptomatic carriers, and 96.1% in healthy individuals. Female sex (p = 0.012), Crohn's disease (p = 0.026), and disease behavior of B3 (p = 0.029) were factors that indicated a lower vaccination rate. A significantly higher proportion of healthy individuals had received one booster dose (76.8%) than asymptomatic carriers (43.4%) and patients with IBD (26.2%). Patients with IBD received vaccination without an increased risk of adverse events (p = 0.768).ConclusionThe vaccination rate of patients with IBD remains much lower than that of asymptomatic carriers and healthy individuals. The COVID-19 vaccine has been found to be safe among all three groups and patients with IBD are not more susceptible to adverse events.